Segregation of Degradable and Non Degradable using Sensor - Selvaraj, Prabakaran; Nithya, NS (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
All around us, from the things we consume to the things we victual can be classified into two groups- degradable and non-degradable. Natural goods like paper, vegetable peels, etc. are degradable products, which mean they can be consumed by the microor- ganisms and returned to the nature. On the other hand, products like glass, synthetic rubber and steel come under the category of non-degradable. These things are not decomposed by the action of microorganisms and they stay in our environment for hundreds of years polluting our land and the whole ecosystem. When we have perceived the damage non-degradable items are provoking on our planet, we have to discover perceptive arrangements keeping in mind the end goal to handle these issues. We certainly cannot ostracize the engenderment and utilization of such materials planari- ty but vary methods can be adopted to avail the planet. To separate the waste so for, we have used different bins with different colors, where some color that indicate non-degradable and some color that denote degradable. It needs the better knowledge for human to segregate the waste material. To avoid this, we proposed the idea to segre- gate degradable and non-degradable wastes from dustbins where the dustbins itself has the knowledge to segregate by using Sensor. The ultrasonic sensor, Metal detection sensor, Plastic detection sensor, Proximity Capacitive sensor to detect glass and paper and are used for segregation and a robotic hand is used to pick and place bins overflow respectively. The Digital IR sensor is to intimate the overflow of the dustbin. Finally, the IOT process is used to intimate the status of the material in the dustbin to the concern person.